Can Apelin-13 be a new actor in control of obesity? - Tekin, S.; Erden, Y.; Etem, E.; Sandal, S.; Colak, C. (Wiley-Blackwell, 2014)
[Abstract Not Available]
Keywords: Apelin; UCP1; UCP3; white adipose tissue; brown adipose tissue